PENGARUH FAKTOR INTERNAL BANK TERHADAP VOLUME KREDIT PADA BANK UMUM YANG TERDAFTAR DI INDONESIA (Students' Journal of Accounting and Banking, 2013)
Banking is a very important part in the economy, one of them as intermediary whose job is to collect funds from the public and channel them back in the form of loans. Credit is something that is important in the economy, especially since some of the financing of investment financed by bank loans. The purpose of this study is to investigate and analyze the effect of CAR, NPL, and LDR to the volume of bank credit.The population in this study is a conventional commercial bank listed in Bank Indonesia during 2009-2011 as many as 86 banks. Samples are determined by purposive sampling technique in order to obtain a sample in accordance with the specified criteria. The sample in this study there are 81 banking companies. This study were analyzed using multiple linear regression analysis.Based on the survey results revealed that partial CAR negative and significant effect. NPL has negative and insignificant. As for the LDR and significant positive effect.Keywords: Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), credit